Implementation of Articles 359 and 360 of the Criminal Code Concerning Negligence Resulting in 132 Casualties in the Arema Vs Persebaya Match - Sunggul Sidabutar; Kusno Kusno; Ahmad Ansyari Siregar (International Journal Labs, 2023)
This study aims to find out and analyze the implementation of articles 359 and 360 of the criminal code regarding negligence resulting in casualties. As well as knowing and analyzing the factors of negligence that resulted in casualties. This research belongs to the normative type of research. So it may be known that whoever by his negligence causes the death of any person shall be punished with imprisonment for not more than five years or imprisonment for not more than one year.